(untitled) (ACME, 2022)
In 1881, the publisher Brigola in Milan printed Macchiette parigine, a collection of biographical profiles that the Sicilian writer Emanuele Navarro della Miraglia (1838-1919) dedicated to eminent figures in French literary and artistic culture in the mid-19th century. A scholar in French studies, long resident in Paris (1864-1872), in contact with the Lombard Scapigliatura in Milan (1872-1882) and finally professor of French language and literature at the Istituto Superiore di Magistero Femminile in Rome (1883-1913), Navarro della Miraglia’s “macchiette” also included two portraits of artists, dedicated respectively to Gustave Courbet and Jean-Baptiste Carpeaux. The aim of this contribution is to define the context and the consequences of an interpretation that is not in line with the more “orthodox” discussion of Courbet’s lesson promoted by Diego Martelli among the Tuscan Macchiaioli, for the benefit of a cultural geography differently articulated between the cosmopolitan openings of southern naturalism and the most advanced fringes of Lombard Scapigliatura. In the same way, the account of Carpeaux’s atelier is reconsidered in the light of the contemporary debate on monumental sculpture and a more animated and nervous modelling in the on-going artistic production in Milan.